ECONOMIC ANALYSIS OF ECOSYSTEM COMPETITION IN THE DIGITAL PAYMENTS MARKET (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The current stage of digitalization of the economy leads to radical changes in the financial sector, especially in the field of payment solutions. Digital payment platforms play a key role in transforming the ways of interaction between business, government and consumers. This article aims to comprehensively analyze the competitive environment in the digital payments market with an emphasis on platforms such as Click, Payme and Stripe. The mechanisms of the ecosystemfunctioning, market strategies are revealed, and a quantitative assessment of their economic efficiency is carried out. Particular attention is paid to statistical modeling, methods for calculating the market profitability of platforms, and an assessment of the role of digital payments in macroeconomic development.